Organic photovoltaics’ new renaissance: advances toward roll-to-roll manufacturing of non-fullerene acceptor organic photovoltaics - Ng, Leonard W. T. (2022)
Non-fullerene acceptors (NFAs) have recently breathed new life into organic photovoltaic (OPVs), achieving breakthrough photovoltaic conversion efficiencies. Unlike conventional fullerene acceptors, they offer strong levels of tunability and solution-processibility that allow them to be easily exploited in the roll-to-roll (R2R) fabrication process. This has enabled a new renaissance for OPVs in the face of other photovoltaic material candidates for large-scale, high-throughput, cost-effective manufacturing. In this review, the current progress of R2R manufacturing of NFA-OPVs and the applications enabled by them are summarized. The perspectives on their research, technological, and future prospects for industry scale-up are also presented.